Peningkatan Minat Penggunaan Produk Keuangan Syariah Melalui Islamic Branding dan Literasi Keuangan Syariah - Rihfenti Ernayani (ITB AAS INDONESIA Surakarta, 2023)
This research is motivated by the importance of interest in using Islamic financial products. This study aims to identify and analyze the increased interest in using Islamic financial products through Islamic branding and Islamic financial literacy. The research method used in this research is descriptive research with a quantitative approach. The sample in this study was 98 people with a random sampling technique. Data collection techniques through observation, questionnaires and questionnaires. The instruments used have been tested for validity, reliability and classic assumption tests. The collected data were analyzed using multiple linear regression with the help of SPSS and Excel. The results of this study indicate that 1) Islamic branding has a positive and significant effect on increasing interest in using Islamic financial products, 2) Islamic financial literacy has a positive and significant effect on increasing interest in using Islamic financial products, and 3) Islamic branding and Islamic financial literacy together the same positive and significant effect on increasing interest in the use of Islamic financial products. The findings of this study indicate that if you want to increase interest in using Islamic financial products, Indonesian Sharia Banks must increase Islamic branding and Islamic financial literacy.